Obliterating Airway Bronchus Sign of Occult Malignancy in Sarcoid Conglomerate Fibrotic Masses - McVeigh,Niall; Murphy,David J.; McKone,Edward; Dodd,Jonathan D. (Journal of Clinical Imaging Science)
Sarcoidosis is a multiorgan disease which presents in up to 95% of cases with lung involvement, a proportion of which develops conglomerate fibrotic masses (CFMs). CFMs typically progressively increase in size overtime. The development of a lung malignancy within a CFM is rare and difficult to diagnose within the underlying lung fibrosis. Here, we describe the obstructing airway bronchus sign in CFMs as an important part of assessing CFMs overtime on computed tomography, which when it occurs should raise suspicion of an occult underlying carcinoma.